Literacy Assessment Merging Teaching, Learning, and Assessment - Griffin, Patrick ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1991)
Data from research studies seem to support the validity of teacher judgments of student achievement; however, there are unresolved issues, including the focus of the judgment, the external validity or credibility of the assessment, and the process of the assessment itself. To achieve maximum benefits from this form of assessment/teaching interface, teachers may need to be sensitized to the extent and importance of the assessment role in the teaching process. Intensive experience with basic principles of measurement and assessment instruments and other devices is needed. Effective teaching is based on an ability to assess accurately: assessment does and should inform the teaching process. It becomes more powerful as the assessment becomes integrated into teaching. The more a teacher uses intuitive judgement and direct observation of a student's literacy development, the more powerful the assessment becomes in the classroom. The key to the development of a cohesive and coherent set of assessment tasks all directed toward the same developmental aim is the existence of a criterion scale of development that can be used to link the teaching and learning process and the interpretation of assessment information. Linking assessment and reporting to teaching and learning is facilitated by the use of descriptive criterion scales which standardize the reporting terminology. The link between teaching, learning, and assessment, while having an undeniable internal validity, may at times need an external reference to establish external validity. (Two figures are included; 27 references are attached.) (RS)
ERIC Note: Paper presented at the Annual Meeting of the International Reading Association (36th, Las Vegas, NV, May 6-10, 1991).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Criterion Referenced Tests; Educational Assessment; Elementary Secondary Education; Literacy; Standardized Tests; Student Evaluation; Test Use; Test Validity; Teacher Judgments; Speeches/Meeting Papers; Information Analyses